The potential effects of microplastic pollution on human digestive tract cells - Zhang, Yuting; Wang, Shunlan; Olga, Volovych; Xue, Yijia; Lv, Shuguo; Diao, Xiaoping; Zhang, Yingai; Han, Qian; Zhou, Hailong (Chemosphere (Oxford), 2022)
The level of environmental microplastics in the biosphere is constantly increasing. These environmental microplastics can enter the human body with food, be absorbed through the gut, and have negative effects on the organism health after its digestion. Four sizes (0.1, 0.5, 1, 5 μm) polystyrene microspheres (PS-MPs) and nanospheres (PS-NPs) were selected for this study. The effects of different sizes of polystyrene particles on human colonic epithelial cell CCD841CoN and small intestinal epithelial cell HIEC-6 within 24 h were explored. The uptake of PS-NPs was found to has more potential to enter cells than micro-sized polystyrene PS-MPs that was confirmed by fluorescence microscope, and the intake amount was proportional to the exposure time. PS-MPs had no significant effect on cell viability and apoptosis, but the group treated with high concentration showed low toxicity to oxidative stress level and mitochondrial membrane potential. In addition, the membrane damage caused by PS-MPs was significantly higher than that of PS-NPs. This may be due to the large amount of polystyrene adhering to interstitial, which have a significant negative effect on the cell membrane functions. For the first time human intestinal normal cell lines were used to study the effect of microplastic pollution, which can provide some references for the influence of microplastics on human health in the future. [Display omitted] •Nano-polystyrene enters cells more easily than micro-polystyrene.•The intake amount of microplastic was proportional to the exposure time.•The 0.1–5 μm polystyrene showed low toxicity to CCD841CoN and HIEC-6 cells.•5 μm polystyrene can cause mitochondrial depolarization.•The membrane damage caused by PS-MPs was significantly serious than that of PS-NPs.